Another new species of the genus Dahlia (Asteraceae, Coreopsideae): are we close to knowing its total diversity? - Reyes-Santiago, Jerónimo; Ortiz-Brunel, Juan Pablo; Lichter-Marck, Isaac H.; Castro-Castro, Arturo (Instituto de Ecología, A.C., 2024)
Background and Aims: The genus Dahlia is culturally and economically appreciated. The botanical explorations in richness areas for Dahlia still provide taxonomic novelties. The aims of this communication are to describe the new species D. gypsicola, and compare it morphologically and ecologically with D. calzadana, providing a distribution map, illustrations, an identification key for Dahlia of the Cañada-Mixteca biocultural region in Oaxaca, Mexico, and a species accumulation analysis. Methods: Our study was based on field exploration, herbarium material revision, and analysis of living collections. The conservation status was determined based on range size, and criteria and categories of the IUCN Red List. To measure the sampling effort, a predictive species richness analysis was calculated considering 41 taxa of Dahlia and 2297 herbarium records collected between 1791-2021. Key results: Dahlia gypsicola is a member of Dahlia section Dahlia, morphologically related to D. calzadana. It differs by the herbaceous habit, semi-succulent leaves and stems, smaller petioles and capitulum, more capitula per synflorescence, and fewer disk florets per capitulum. Moreover, both species are allopatric and do not share ecological preferences and phenology. The category of Critically Endangered (CR B1a) is proposed for D. gypsicola, and Endangered (EN B1a) for D. calzadana. The species prediction richness shows that the number of known Dahlia species is almost complete: the inventory is approaching 95% and the predicted number of species is close to 43. Conclusions: A complete knowledge of the diversity in Dahlia could enhance plant breeding programs with economic and cultural impacts, because the possibilities of generating new cultivars are many. It is recommended to continue the explorations and increase botanical collections; undescribed species may exist where gypsophyte centers of endemism overlap with richness areas of Dahlia.